2012
DOI: 10.1603/en12212
|View full text |Cite
|
Sign up to set email alerts
|

Partial Life Tables From Three Generations of <I>Enaphalodes rufulus</I> (Coleoptera: Cerambycidae)

Abstract: We used life table analyses to investigate age specific mortality and to better understand the population dynamics of the red oak borer, Enaphalodes rufulus (Haldeman) (Coleoptera: Cerambycidae). We continually sampled populations within 177 trees at primarily two sites in the Ozark National Forest in Arkansas throughout three (2-yr) generations. The first cohort (adults emerged in 2003) was sampled during a severe population outbreak, whereas the second and third (2005 and 2007) were sampled during the popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…High levels of early-stage mortality indicate that initial conditions in pines were very important for Sirex survival. This same trend was reported from life tables of other wood-inhabiting insects [ 49 52 ]. It follows that mechanisms of tree resistance would be most effective at the early stages of insect attack: female oviposition or larval establishment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…High levels of early-stage mortality indicate that initial conditions in pines were very important for Sirex survival. This same trend was reported from life tables of other wood-inhabiting insects [ 49 52 ]. It follows that mechanisms of tree resistance would be most effective at the early stages of insect attack: female oviposition or larval establishment.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, tree resistance appears to be the most important factor limiting populations of many bark- and wood-boring insects (e.g. [ 52 56 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Hay reported both 33% (1972) and 40% (1974) early instar mortality of E. rufulus occurring while larvae were feeding in the phloem immediately under the bark. A much lower percentage occurred in a study by Petit et al (1988) on the predation of later instars when they were 3–7 cm under the bark and Haavik et al (2012) observed a single probable attack in 3 generations. The success of bird predation also relies quite heavily on accessibility.…”
Section: Discussionmentioning
confidence: 80%
“…Between late summer of the first year and the following spring, during which time SMB larvae extended their galleries to about 30 cm and overwintered for the first time, 27% died. Sources of mortality for other tree-inhabiting cerambycids over a comparable period in their life history include intraspecific competition (Hanks et al 2005— P. semipunctata ), production of scar tissue by the tree (Haavik et al 2012— E. rufulus ), interspecific competition, fermenting medium or wound sap and the nitidulids it attracted, and woodpecker predation (Hay 1974— E. rufulus ). Only woodpecker predation was substantiated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Enaphalodes rufulus larvae were shown to be facultative intraguild predators in a laboratory setting (Ware and Stephen 2006). If facultative predation also occurred in field scenarios, that behaviour may account for some proportion of E. rufulus larval mortality attributed to unknown causes (Haavik et al 2012a). These interactions may affect both how female E. rufulus choose to distribute oviposition on selected hosts and the survival of E. rufulus larvae.…”
Section: Introductionmentioning
confidence: 99%